Supplementation of nitrocompounds in broiler diets: Effects on bird performance, ammonia volatilization and nitrogen retention in broiler manure. Issue 2 (1st February 2016) - Mowrer, Jake E.; Sedlacek, Paula; Kim, Jihyuk; Ritz, Casey; Kim, Woo. K.
ABSTRACT: A study was conducted to evaluate the effects of dietary nitrocompounds on bird performance, ammonia volatilization, and changes in manure nitrogen (N). A total of 200 one-day-old male chicks (Cobb 500) were used for this study. The chicks were raised in electrically heated battery brooders for 18 days. On day 1, birds were allocated into five treatment groups with four replicated pens: (T1) control, a corn and soybean meal diet (3, 100 kcal kg −1 metabolizable energy (ME) and 21% Crude Protein (CP)); (T2) 16.7 mg kg −1 nitroethanol (NEL); (T3) 33.3 mg kg −1 NEL; (T4) 16.7 mg kg −1 nitropropanol (NPL); and (T5) 33.3 mg kg −1 NPL. The body weight gain, feed intake and feed efficiency were measured on days 7, 14 and 18. Volatized ammonia (VA) and other N forms were measured at collection and following 2 weeks of incubation at 30°C. Broiler growth was not adversely affected by the nitrocompounds at concentrations up to 33.3 mg kg −1 . The results show that initial manure pH was reduced by adding nitroethanol (NEL) and nitropropanol (NPL) to the diet by 0.2 and 0.5 pH units, respectively. Total VA after 2 weeks was unaffected by dietary treatment. The amounts of uric acid decomposed and ammonia produced were closely balanced in the control sample. However, this balance was significantly different among the manures produced by birds receiving nitrocompound treatments. The inclusion of NEL and NPL resulted in the presence of measurable amounts of Xanthine not found in the control group. This study indicates that supplementation of nitroethanol or nitropropanol into broiler diets up to 33.3 mg kg −1 influences uric acid degradation and ammonia production in broiler manure while maintaining optimal growth performance.